LEVEL OF RURAL WOMAN KNOWLEDGE IN DOMAIN FOOD INDUSTRIES AND ITS RELATION WITH SOME VARIABALES FIELD STUDY IN THE TWO VILLAGES: OF AL SHRAIKHAN AND - Zeki H. Al-Leela (Mesopotamia Journal of Agriculture)
The present study aims basically at an assessing of the knowledge of rural women in food industries domain. The research also aims at specifying the relationship or differences between rural woman knowledge and the independent related variables. Women in the two villages of Al-Shraikhan and Qubba in Nineveh governorate. Random sample representing 10% data were collected by using questionnaire (a test method) prepared specially to asses the knowledge of rural women in this domain, the first part consists of independent variables, while the second consists a test to measure rural women knowledge level in food industries domain which consists (16) items regarding with different food industries . After testing its validity, reliability was measured using half spilt half method. Data then were analysized by using statistical tools: Mean, person coefficient, Man -wittny, and Stepwise Regression. The results showed that 83.33% of rural women have middle to high level knowledge, the results also showed that the knowledge level of the respodens in food industries domain was not related to: age, family level of education, family previous work, and number of family members working in food industries. The level of the respodens, standard of living, and sources of information depended on in that particular domain